A metallo-β-lactamase enzyme for internal detoxification of the antibiotic thienamycin - Seydina M. Diene (Nature Portfolio, 2021)
Abstract Thienamycin, the first representative of carbapenem antibiotics was discovered in the mid-1970s from soil microorganism, Streptomyces cattleya, during the race to discover inhibitors of bacterial peptidoglycan synthesis. Chemically modified into imipenem (N-formimidoyl thienamycin), now one of the most clinically important antibiotics, thienamycin is encoded by a thienamycin gene cluster composed of 22 genes (thnA to thnV) from S. cattleya NRRL 8057 genome. Interestingly, the role of all thn-genes has been experimentally demonstrated in the thienamycin biosynthesis, except thnS, despite its annotation as putative β-lactamase. Here, we expressed thnS gene and investigated its activities against various substrates. Our analyses revealed that ThnS belonged to the superfamily of metallo-β-lactamase fold proteins. Compared to known β-lactamases such as OXA-48 and NDM-1, ThnS exhibited a lower affinity and less efficiency toward penicillin G and cefotaxime, while imipenem is more actively hydrolysed. Moreover, like most MBL fold enzymes, additional enzymatic activities of ThnS were detected such as hydrolysis of ascorbic acid, single strand DNA, and ribosomal RNA. ThnS appears as a MBL enzyme with multiple activities including a specialised β-lactamase activity toward imipenem. Thus, like toxin/antitoxin systems, the role of thnS gene within the thienamycin gene cluster appears as an antidote against the produced thienamycin.